2010
DOI: 10.1136/jnnp.2010.206680
|View full text |Cite
|
Sign up to set email alerts
|

Home telemonitoring of non-invasive ventilation decreases healthcare utilisation in a prospective controlled trial of patients with amyotrophic lateral sclerosis

Abstract: This study shows that telemonitoring reduces health care utilisation with probable favourable implications on costs, survival and functional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 35 publications
2
96
0
5
Order By: Relevance
“…Lechtzin et al reported a retrospective study on 102 ALS patients and found a survival advantage of 1 year in those provided intervention early (forced vital capacity [FVC] > 65%) [21]. Pinto et al presented similar data in patients who were started on NIPPV because of nocturnal desaturations but not diminished FVC [22]. Patients in this study receiving early intervention also survived longer than those provided the intervention later.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Lechtzin et al reported a retrospective study on 102 ALS patients and found a survival advantage of 1 year in those provided intervention early (forced vital capacity [FVC] > 65%) [21]. Pinto et al presented similar data in patients who were started on NIPPV because of nocturnal desaturations but not diminished FVC [22]. Patients in this study receiving early intervention also survived longer than those provided the intervention later.…”
Section: Introductionsupporting
confidence: 67%
“…Pinto et al reported that in ventilated ALS patients, home telemonitoring resulted in decreased emergency room visits and hospital admissions, with a trend toward increased survival [22]. We are currently following eight patients via telemedicine and four patients using mobile video consultation.…”
Section: Telemedicine and Mobile Video Consultationmentioning
confidence: 99%
“…A prospective, single-blind controlled trial [9] of home noninvasive ventilation (NIV) in amyotrophic lateral sclerosis (ALS), showed that compliance to NIV with or without tele-monitoring was similar, whereas NIV initial setting was successfully managed by tele-monitoring. This study showed also that tele-monitoring might offer potential favourable effects on costs, survival and functional status.…”
Section: Neuromuscular Diseasesmentioning
confidence: 99%
“…It was considered an effective ventilation whether patient presented fingertip pulse oximetry>96%, and heart rate between 60-80 bpm under NIV during the medical consultation, with further analyses of satisfactory parameters of nocturnal percutaneous pulse oximetry as aforementioned. [18,19]; and we recorded data of compliance and each ventilation settings changes throughout NIV use [20]. All samples were fully compliant to NIV.…”
Section: Functional Assessmentmentioning
confidence: 99%